Predictive models of going concerns and business failure - Paul Hammond; Mustapha Osman Opoku; Paul Adjei Kwakwa; Edmond Amissah (Cogent Business & Management, 2023)
Given the global attention and attraction of many scholars and researchers to develop prediction models for determining the going concern of businesses, there is a growing need to monitor progress and trends in the field. As such, the study aims to analyse the evolution of prediction models for going concern and business failure in the literature over the past 50 years. The study used VOSviewer and the biblioshiny utility of RStadio to analyse bibliometric data extracted from the Scopus database. The results indicated that there was a slow pace in publications from the 1970s to 1999, but the number of publications increased in the 2000s and continues to increase. The study also found that many countries across the globe have significantly contributed to modelling going concerns and business failure predictions. Furthermore, the visualisation of bibliographic coupling and co-occurrence of the author's keywords revealed knowledge drifts in the field's interconnected publications with many collaborations. The analysis of the author's keywords revealed key themes such as going concern probability, the omega model, and business failure probability that remained under-researched and that research attention should be directed to that areas. These findings shed light on the research trends, influential works, author contributions, global perspectives and the current state of research in the field and provide valuable insights for future studies in the prediction of going-concern and business failure.
Keywords: 650; Bankruptcy; bibliometric analysis; business failure; going concern; survival